Stretching - Roberts, Melanie (Fitness researcher); Kaiser, Stephanie (Idiot's guides., 2013)
Stretching is relaxing and revitalizing, and helps increase your flexibility and range of motion. But stretch the wrong way and you could be doing yourself more harm than good! This guide teaches you the correct way to stretch, so you can avoid common stretching mistakes.--Source other than Library of Congress.